BiOI nanosheets with dominated (001) facet and its photocatalytic performances. (27th July 2019) - Shan, Lianwei; Xiao, Yanwei; Bi, Jingjing; Lu, Changhui; Wu, Ze
Abstract: We synthesized BiOI(001)/cocatalysts composites, selective deposition of cocatalysts were demonstrated to be an effective method to improve their photocatalytic performance. Ag nanoparticles were grown on the surfaces of the pre-synthesized BiOI(001) nanosheets through a photodeposited process. The work demonstrates that the as-synthesized sample is a promising photocatalyst for the treatment of MO. The enhanced photocatalytic activity is attributed to the charge transfer from BiOI(001) to the attached Ag nanoparticles.